PERBANDINGAN HASIL BELAJAR PESERTA DIDIK YANG MENGGUNAKAN MODEL PEMBELAJARAN INQUIRY DENGAN MODEL PEMBELAJARAN DISCOVERY PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 GELUMBANG - Heni Sintia; Riswan Jaenudin; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2019)
This research entitled "Comparison of Learning Results Students Between Using Inquiry Learning Model with Learning Models Discovery on Economics Class X class at SMA Negeri 1 Gelumbang". The problem formulation is “whether there are differences in learning outcomes of learners between using the model of learning inquiry with the model of learning discovery on the subjects of economy class X in SMA Negeri 1 Gelumbang”. This research is a comparative study, which uses a compeletely randomized design design, with a pretest posttest form. Population in this research is all class X in SMA Negeri 1 Gelumbang. The sample used cluster random sampling, so selected X class IPS 2 as experiment class 1 which amounted to 32 students and X IPS 3 as experiment class 2 amounted to 30 students. Data collection techniques used are tests and observations. Hypothesis using parametric statistic that is test-t and obtained tcount value bigger than table or 2,692 bigger than 1,671 hence hypothesis of Ho refused and Ha accepted. It can be concluded that there are differences in learning outcomes of learners between using the model of learning Inquiry with the model of learning Discovery on the subjects of economy class X in SMA Negeri 1 Gelumbang.